2010
DOI: 10.1038/nbt.1615
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution DNA analysis of human embryonic stem cell lines reveals culture-induced copy number changes and loss of heterozygosity

Abstract: Prolonged culture of human embryonic stem cells (hESCs) can lead to adaptation and the acquisition of chromosomal abnormalities, underscoring the need for rigorous genetic analysis of these cells. Here we report the highest-resolution study of hESCs to date using an Affymetrix SNP 6.0 array containing 906,600 probes for single nucleotide polymorphisms (SNPs) and 946,000 probes for copy number variations (CNVs). Analysis of 17 different hESC lines maintained in different laboratories identified 843 CNVs of 50 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
146
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(161 citation statements)
references
References 39 publications
13
146
0
Order By: Relevance
“…A recent study compared early and late passages of hESC lines and reported about high rate of copy number variations and loss of heterozygocity changes. 37 Taken together, these findings emphasize the need of tight surveillance of genomic integrity during long-term culture and the preference of low passages for clinical applications.…”
Section: Aneuploidy Screeningmentioning
confidence: 89%
“…A recent study compared early and late passages of hESC lines and reported about high rate of copy number variations and loss of heterozygocity changes. 37 Taken together, these findings emphasize the need of tight surveillance of genomic integrity during long-term culture and the preference of low passages for clinical applications.…”
Section: Aneuploidy Screeningmentioning
confidence: 89%
“…Overall, even though iPSC obviously need to pass through one additional selection process, reprogramming, iPSC and ESC are not drastically different considering the mutational load. In addition, there is some correlation between mutations found in late passage human ESC, iPSC, and cancers cells [75][76][77]. Thus, pluripotent cells cultured in vitro are by definition proliferating and can acquire specific aberrations that support growth advantage, similar to tumor progression, that eventually take over the population.…”
Section: Mutational Load Of Ipscmentioning
confidence: 99%
“…Though, among 17 lines analysed by Närvä et al (2010) one, FES 21, had identical q arms on chromosome 16, whereas all others had a heterozygous set of chromosomes.…”
Section: Upd-a Form Of Lohmentioning
confidence: 99%
“…Despite wide interest in defining the properties of hESCs, comprehensive characterization has been done with only a subset of lines. The popularity of some of the earliest lines derived, such as H1 and H9, both for research and for the generation of clinical grade banks, arises not necessarily because they are superior lines, as these cells were derived on mouse feeders in the presence of serum, but because by default (Adewumi et al 2007;Allegrucci & Young 2007;Lefort et al 2008;Närvä et al 2010). Although many of such studies have been useful in identifying 'master' genes of pluripotency, no consistent clustering could be ascribed to variations in chromosomal stability or differentiation propensity of the hESC lines.…”
Section: Risk Assessment Of Genetic Abnormalities In Hesc-based Cell mentioning
confidence: 99%
See 1 more Smart Citation